Structural Changes and Agricultural Sector in V4 Countries – Input-Output Analysis - ĎURČOVÁ, Júlia; ORAVCOVÁ, Dominika (Journal of Environmental Management and Tourism, 2020)
The path of further development of agriculture is a key factor for the future of the European environment. Due to intensifying fragmentation of production activities that have a significant effect on the production structure of the national economies, this traditional sector was offset by machinery production in terms of output and job creation. Moreover, the agricultural sector in V4 countries has its own specifics and its position significantly changed compared to previous socialist system. Therefore the main objective of this paper is to investigate the changes and effect of agricultural sector on employment creation in V4 countries i.e. Poland, Hungary, Czech Republic and Slovakia during period 2000-2014. Our analysis relies on input-output model using input-output tables from WIOD database. The results indicate declining impact on national job creation although the position of agricultural sector in V4 countries (mainly in Poland) is still significant.